Study on the Factors Influencing the Amplitude of Local Ice Pressure on Vertical Structures Based on Model Tests - Ying Xu; Dayong Zhang; Kuankuan Wu; Xin Peng; Xunxiang Jia; Guojun Wang (Journal of Marine Science and Engineering, 2024)
Local ice pressure refers to the ice pressure exerted on a very small area of a structure during ice failure. The existence of high-pressure zones may lead to local deformation and damage to ice-resistant structures, posing a serious threat to the overall structural stability. This study simulates the interaction between sea ice and structures through model tests, analyzing the timing of extreme local ice pressures. The results show that at low loading speeds, there is a 50% probability that the extreme local ice pressure occurs at the peak of the global ice force, while at high loading speeds, this probability drops to around 25%. Further investigation into the relationship between the global ice force peak, ice thickness, loading speed, and local area with local ice pressure amplitude reveals that the local ice pressure amplitude decreases with increasing loading speed and increases with ice thickness. Based on the area averaging method for square regions, the relationship between local ice pressure amplitude and local area is studied, showing that ice thickness, local width, and loading speed all influence the pressure–area relationship. Based on the square area averaging method, the relationship between the local ice pressure amplitude and the local area was studied. It was found that a linear relationship exists between the power function coefficient of local ice pressure–area and the thickness-to-width ratio. Compared to brittle failure, the local ice pressure amplitude under ductile failure of the ice sheet is more significantly affected by ice thickness. This study provides a foundation and reference for the analysis of ice-resistant performance and structural design of polar marine engineering structures.